Backwardness and modernization through technology – CCTV in Portugal - Frois, Catarina (EXCHANGE SUMMER SCHOOL “Surveillance Technologies, Criminality, and Human Rights”, 2018)
In Portugal between 2005 and 2010, “modernization through technology” was the major political motto used to develop and improve the country’s peripheral and backward condition. This class explores one of the resulting, specific aspects of this trend—the implementation of public video surveillance. Taking ethnographic material as basis, it will show how the political construction of security and surveillance as a strategic program actually conceals intricate institutional relationships between political decision-makers and common citizens. Essentially, the detailed account of the major actors, as well as their roles and motivations, serves to explain phenomena such as the confusion between objective data and subjective perceptions or the lack of communication between parties, which as it will be argued, underlies the idiosyncrasies and fragilities of Portugal’s still relatively young democratic system.